Analytical Study for Comparing Social Attitude Scale among Advance Scouting Teams in Baghdad Governorate Bureaus - Abdul Hussein, Haider; Nebhan, Neda (Journal of Physical Education, 2020)
The importance of the research lies in designing a psychological attitude scale for participating in scouting activities of advance scouting teams in Baghdad governorate bureaus. Tests and scales play an integral role in diagnosing, classifying, and following scouting teams. The research aimed at identifying advance scouting plans for general service project and executing these aims. The researchers used the scanning method on (176) school scouts from Baghdad bureau. A questionnaire was designed and presented to experts them distributed on the subjects of the study to conclude five axes for measuring social attitude scale.